2009
DOI: 10.4049/jimmunol.0803313
|View full text |Cite
|
Sign up to set email alerts
|

A20 Negatively Regulates T Cell Receptor Signaling to NF-κB by Cleaving Malt1 Ubiquitin Chains

Abstract: The Carma1-Bcl10-Malt1 signaling module bridges TCR signaling to the canonical IκB kinase (IKK)/NF-κB pathway. Covalent attachment of regulatory ubiquitin chains to Malt1 paracaspase directs TCR signaling to IKK activation. Further, the ubiquitin-editing enzyme A20 was recently suggested to suppress T cell activation, but molecular targets for A20 remain elusive. In this paper, we show that A20 regulates the strength and duration of the IKK/NF-κB response upon TCR/CD28 costimulation. By catalyzing the removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
200
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 217 publications
(213 citation statements)
references
References 41 publications
10
200
3
Order By: Relevance
“…It has been shown that in T cells, MALT1 protease activity is required for optimal NF-κB activation and induction of target genes, but is dispensable for IKK/NF-κB upstream signaling (6,7). Thus, the stage of NF-κB activation controlled by PI3K-PDK1-MALT1 remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in T cells, MALT1 protease activity is required for optimal NF-κB activation and induction of target genes, but is dispensable for IKK/NF-κB upstream signaling (6,7). Thus, the stage of NF-κB activation controlled by PI3K-PDK1-MALT1 remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…However, T-cells and B-cells constitutively express considerable high levels of A20, which inhibits ubiquitination of the NF-κB signaling protein MALT1 [70]. In this case, antigen 16 receptor stimulation triggers a rapid decrease and subsequent reappearance of A20, suggesting that A20 removal could be a crucial step in eliminating the negative regulatory activity of A20.…”
Section: Mechanisms Regulating A20 Activitymentioning
confidence: 98%
“…In this case, antigen 16 receptor stimulation triggers a rapid decrease and subsequent reappearance of A20, suggesting that A20 removal could be a crucial step in eliminating the negative regulatory activity of A20. Proteasomal degradation of A20, as well as its cleavage by the paracaspase MALT1, contribute to the decrease in A20, resulting in enhanced IL-2 production and NF-κB activation [70,71].…”
Section: Mechanisms Regulating A20 Activitymentioning
confidence: 99%
“…Previous studies have shown that the OTU domain-containing DUB A20 and the USP domain-containing DUB cylindromatosis protein negatively regulate NF-κB activation through deubiquitination of signaling molecules, such as RIP and TRAF2, in response to innate immune stimulation (5)(6)(7). In adaptive immunity, this is thought to involve ubiquitin-mediated regulation of key components of the T-cell receptor (TCR) signaling machinery, including the Carma1-Bcl10-Malt1 (CBM) complex (8) and Tak1 (9). How the deubiquitination system regulates the TCR-induced signaling pathway and T-cell function remains largely unclear, however.…”
mentioning
confidence: 99%